Media Development Smart Dice for Early Children in TK Syafina Family Kids Tanjung Morawa District - Amanda Cinta Dwi Putri; Novita Frizka (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to develop smart dice media and to find out which smart dice media are feasible and ready to be used as learning media for early childhood at Syafina Family Kids Kindergarten, Tanjung Morawa District. The problems in this study include students being fixated, the learning activities carried out are still conventional, the limited use of learning media in carrying out the learning process so that good communication has not been established. The development research model used in this study is the 4-D development model (Definition, Design, Development, Deployment). The results showed that the development of smart dice media for early childhood was carried out by adopting a 4-D development procedure which consisted of the define stage, the design stage, the development stage, the disseminate stage. This development procedure is adapted to the guidelines for the development of smart dice media so that each stage consists of several processes. The Define stage includes: 1) Analysis of learning needs; 2) See the completeness of the media. The process at the Design stage includes: 1) Arranging learning media needs; 2) Create a predefined product design. The Development stage includes: 1) Guidance by expert lecturers; 2) Validating learning media by material experts, media experts and teachers. The quality of the smart dice media developed based on validation shows a good category.